-1
$\begingroup$

Given this linear transformation:

$f\begin{pmatrix}x\\y\\z\\w\end{pmatrix} = \begin{pmatrix}x + 2y − z + 10w\\2x − y + 3z\\y − z + 4w\end{pmatrix}$.

I want to find its kernel and so I try to solve the following equations system:

Equations system

Finding the next solution:

Solution

However, the solution appears to be incorrect, as the answer to the problem is that the kernel of the transformation is:

Real solution

I can't figure out what i'm doing wrong, please help.

$\endgroup$
  • $\begingroup$ Please use MathJax to type up the question $\endgroup$ – pureundergrad Apr 30 '18 at 20:57
  • $\begingroup$ There’s no such thing as the “real solution.” Any basis for the kernel will do. $\endgroup$ – amd Apr 30 '18 at 21:07
1
$\begingroup$

So the system could be written as $$ f(x,y,z,w) = \begin{bmatrix} 1 & 2 & -1 & 10\\ 2 & -1 & 3 & 0\\ 0 & 1 & -1 & 4\\ \end{bmatrix} \begin{bmatrix} x\\ y\\ z\\ w \end{bmatrix} $$ So let $A$ be the matrix $$ A = \begin{bmatrix} 1 & 2 & -1 & 10\\ 2 & -1 & 3 & 0\\ 0 & 1 & -1 & 4\\ \end{bmatrix} $$ To find the null space (Kernel), we should find all vectors such that $$ \begin{bmatrix} x\\ y\\ z\\ w \end{bmatrix} = \begin{bmatrix} 0\\ 0\\ 0 \end{bmatrix}$$ That is

\begin{align} x + 2y − z + 10w &= 0\\ 2x − y + 3z &= 0\\ y − z + 4w &= 0 \end{align} Last equation suggests that $$z = y + 4w$$ Plugging this equation back we get \begin{align} x + 2y − (y + 4w) + 10w &= 0\\ 2x − y + 3(y + 4w) &= 0 \end{align} that is \begin{align} x + 2y − y - 4w + 10w &= 0\\ 2x − y + 3y + 12w &= 0 \end{align} that is \begin{align} x + y +6w &= 0\\ 2x + 2y + 12w &= 0 \end{align} Multiplying equation 1 by a factor of 2: \begin{align} 2x + 2y +12w &= 0\\ 2x + 2y + 12w &= 0 \end{align} We get the same equation. This means that we have the following dependence: \begin{align} z &= y + 4w \\ x &= -y -6w \end{align} So the kernel is all such vectors $(x,y,z,w)$ such that $z = y + 4w$ and $x = -y-6w$ (which is of dimension 2)

$\endgroup$
0
$\begingroup$

Guide:

Both solutions are fine.

Verify that

$$\operatorname{rref} \left(\begin{bmatrix} -1 & 1 & 1 & 0 \\ -2& -4& 0& 1 \end{bmatrix} \right) = \operatorname{rref}\left(\begin{bmatrix} -1 & 1 & 1 & 0 \\ -6& 0&4 & 1 \end{bmatrix} \right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.